Drug-eluting cements for hard tissue repair: A comparative study using vancomycin and RNPA1000 to inhibit growth of Staphylococcus aureus. (April 2014) - Eidem, Tess M; Coughlan, Aisling; Towler, Mark R; Dunman, Paul M; Wren, Anthony William
Bone cement used in orthopaedic applications can become colonized with bacterial biofilms, resulting in severe medical complications. Consequently, bone cements are often loaded with antibiotics in an effort to prevent bacterial colonization. However, current formulations may not release antibiotics into the environment at sufficient and sustained concentrations required to impede bacterial growth or may be incompatible with antibiotics that are effective against the colonizing organism. Thus, new cement formulation options are needed. This report describes the performance of a novel SiO2 -TiO2 -ZnO-CaO-SrO-based glass polyalkenoate cement as a carrier of antimicrobials active against Staphylococcus aureus, the predominant cause of orthopaedic biofilm-associated infections. The antibiotic vancomycin and a novel Staphylococcus aureus RnpA inhibitor under pre-clinical development, RNPA1000, were included in these studies. Rheological testing characterized the workability of the glass polyalkenoate cement over a range of powder-to-liquid ratios and polyacrylic acid concentrations and revealed that the most suitable powder-to-liquid ratio was 2/1.25 with 40 wt& polyacrylic acid. Loading glass polyalkenoate cement with either 20–30& RNPA1000 or vancomycin prevented bacterial growth. However, longer incubations allowed for Staphylococcus aureus colonies to form near the vancomycin-infused cement, indicating that vancomycin may not be suitable for long-term biofilm inhibition in comparison to RNPA1000. Scanning electron microscopy and energy-dispersive X-ray analyses confirmed successful incorporation RNPA1000 into the cement matrix and were indicative of its slow release. These studies establish a drug-eluting formulation of glass polyalkenoate cement with great potential in orthopaedic implants that incorporates known antibiotics as well as RNPA1000 to prevent growth of the dangerous pathogen Staphylococcus aureus .